Interactions Between Unmarried Fathers and Their Children: The Role of Paternity Establishment and Child-Support Policies - Argys, Laura M; Peters, H. Elizabeth (American Economic Review, 2001)
Interactions between Unmarried Fathers and Their Children: The Role of Paternity Establishment and Child-Support Policies by Laura M. Argys and H. Elizabeth Peters. Published in volume 91, issue 2, pages 125-129 of American Economic Review, May 2001